The relationship between heart rate variability and recovery heart rate in women - Latchman, P.; Gates, G.; Axtell, R.; Lunn, W.; Stachenfeld, N.; Meersman, R. De (Autonomic Neuroscience: Basic and Clinical, 2015)
Keywords: dept.hms

Weightlifting movements from full extension: The snatch and clean - DiSanto, M.; Valentine, G.; Boutagy, N. (Strength and Conditioning Journal, 2015)
Weightlifting movements require sufficient body speed to squat down and catch the barbell. Body speed can only be maximized if the correct positions are reached before the turnover and catch phases. The snatch from full extension (SFFE) and the clean from full extension (CFFE) allow the athlete to transition from the full extension position to a quick squat underneath the barbell. The SFFE and CFFE can be included into the warm-up or cooldown periods of a training session, focusing on the respective lifts. Correct body positions and speed, as opposed to barbell load, should be emphasized.
Keywords: Body speed; Clean; Full extension; Snatch; Weightlifting; dept.hms

Associations Between Ankle-Brachial Index and Cognitive Function: Results From the Lifestyle Interventions and Independence for Elders Trial - Espeland, M.A.; Newman, A.B.; Sink, K.; Gill, T.M.; King, A.C.; Miller, M.E.; Guralnik, J.; Katula, J.; Church, T.; Manini, T.; Reid, K.F.; McDermott, M.M.; et al. (Journal of the American Medical Directors Association, 2015)
Objective: The objective of this study was to evaluate cross-sectional and longitudinal associations between ankle-brachial index (ABI) and indicators of cognitive function. Design: Randomized clinical trial (Lifestyle Interventions and Independence for Elders Trial). Setting: Eight US academic centers. Participants: A total of 1601 adults ages 70-89 years, sedentary, without dementia, and with functional limitations. Measurements: Baseline ABI and interviewer- and computer-administered cognitive function assessments were obtained. These assessments were used to compare a physical activity intervention with a health education control. Cognitive function was reassessed 24 months later (interviewer-administered) and 18 or 30 months later (computer-administered) and central adjudication was used to classify individuals as having mild cognitive impairment, probable dementia, or neither. Results: Lower ABI had a modest independent association with poorer cognitive functioning at baseline (partial r= 0.09; P < .001). Although lower baseline ABI was not associated with overall changes in cognitive function test scores, it was associated with higher odds for 2-year progression to a composite of either mild cognitive impairment or probable dementia (odds ratio 2.60 per unit lower ABI; 95% confidence interval 1.06-6.37). Across 2 years, changes in ABI were not associated with changes in cognitive function. Conclusion: In an older cohort sedentary individuals with dementia and with functional limitations, lower baseline ABI was independently correlated with cognitive function and associated with greater 2-year risk for progression to mild cognitive impairment or probable dementia. © 2015 AMDA - The Society for Post-Acute and Long-Term Care Medicine.
Keywords: Aged; Aged, 80 and over; Ankle Brachial Index; Ankle-brachial index; Article; Cognition; Cognitive function; Cross-Sectional Studies; Dementia; Disability Evaluation; Exercise; Female; Geriatric Assessment; Health Education; Humans; Male; Mini Mental State Examination; Peripheral artery disease; Sedentary Lifestyle; United States; aged; ankle brachial index; clinical trial; cognition; controlled study; cross-sectional study; dementia; dept.hms; disability; episodic memory; executive function; exercise; female; follow up; geriatric assessment; health education; human; human experiment; learning; longitudinal study; male; mild cognitive impairment; multicenter study; normal human; physical activity; physical performance; randomized controlled trial; recall; sedentary lifestyle; spatial orientation; very elderly; working memory

Lower Wingate Test Power Outcomes from "all-Out" Pretest Pedaling Cadence Compared with Moderate Cadence - Lunn, W.R.; Zenoni, M.A.; Crandall, I.H.; Dress, A.E.; Berglund, M.L. (Journal of Strength and Conditioning Research, 2015)
The aim of the present study was to determine the effect of different pretest pedaling cadences on power outcomes obtained during the Wingate Anaerobic Test (WAnT). Vigorously exercising adult men (n 14, 24.9 ± 1.2 years) and women (n 14, 20.4 ± 0.6 years) participated in a randomized crossover study during which they performed the 30-second WAnT on a mechanically braked cycle ergometer (0.075 kg·kg-1 body weight) under 2 conditions. Participants pedaled maximally with an unloaded flywheel during 5 seconds before resistance was applied and the test began (FAST). In another trial, participants maintained a moderate cadence (80 revolutions per minute [rpm]) during 5 seconds before the test began (MOD). All other components of the WAnT were identical. Peak power (PP), mean power (MP), minimum power (MinP), fatigue index (%FAT), and maximum cadence during test were recorded. Comparisons were made using a 2 × 2 factorial repeated-measures analysis of variance. Regardless of gender, the FAST condition resulted in 22.2% lower PP (612.6 ± 33.0 W vs. 788.3 ± 43.5 W), 13.3% lower MP (448.4 ± 22.2 W vs. 517.2 ± 26.4 W), 11.7% lower MinP (280.9 ± 14.8 W vs. 318.3 ± 17.2 W), and 9.0% lower %FAT (53.5 ± 1.3% vs. 58.8 ± 1.5%) than MOD condition (p < 0.01; mean ± SD). Similar outcomes were observed within gender. The authors conclude that practitioners of the WAnT should instruct participants to maintain a moderate pedal cadence (∼80 rpm) during 5 seconds before the test commences to avoid bias from software sampling and peripheral fatigue. Standardizing the pretest pedal cadence will be important to exercise testing professionals who compare data with norms or generate norms for specific populations. © 2015 National Strength and Conditioning Association.
Keywords: Adult; Bicycling; Cross-Over Studies; Exercise; Exercise Test; Fatigue; Female; Humans; Male; Young Adult; adult; anaerobic; controlled study; crossover procedure; cycling; dept.hms; ergometry; exercise; exercise test; fatigue; female; human; male; muscle; pathophysiology; peer-reviewed; physiology; procedures; randomized controlled trial; young adult

Fish oil supplementation is associated with improved physical function and reduced mobility disability - Gundermann, D. M.; Hire, D. G.; Ambrosius, W. T.; Kritchevsky, S. B.; Pahor, M.; Axtell, R. S.; Newman, A. B.; Manini, T. M. (Gerontologist, 2015)
Keywords: dept.hms; peer-reviewed; ⛔ No DOI found

The relationship between indices of parasympathetic nervous activity and cardiovascular health in men - Latchman, P; Gates, Gregory J; Thiel, Robert; Hannah, C; Stachenfeld, Nina S; Meersman, R De (Autonomic Neuroscience: Basic and Clinical, 2015)
Keywords: dept.hms

Effectiveness of a hybrid classroom in the delivery of medical terminology course content relative to a traditional classroom format - Martin, Jeffrey S; Kreiger, Joan E; Apicerno, Amy L (Journal of the Scholarship of Teaching and Learning, 2015)
Keywords: dept.hms